Leaf Spot Diseases of Strawberry - Juliana S. Baggio; James C. Mertely; Natalia A. Peres (EDIS, 2020)
Several different fungi and one bacterium cause leaf spot diseases of Florida strawberry. Symptoms caused by these pathogens are often similar, leading to confusion and misdiagnosis of the disease. To facilitate diagnosis, the most common leaf spots diseases of strawberry in Florida are described in this new 6-page article, written by Juliana S. Baggio, James C. Mertely, and Natalia A. Peres, and published by the UF/IFAS Plant Pathology Department. https://edis.ifas.ufl.edu/pp359